Advanced Squamous Cell Carcinoma Arising from an Extensive Post‑Burn Scar: Clinical Case - M. M. Zamilov; K. V. Menshikov; R. I. Latypov; D. R. Akhmerov; R. I. Gimatdinov; S. I. Musin; G. I. Zamilova; R. T. Ayupov (Креативная хирургия и онкология, 2025)
Introduction. Squamous cell carcinoma (SCC) is the second most prevalent form of skin cancer, following basal cell carcinoma. The development of SCC on scarred tissue leads to a more aggressive form of the disease, characterized by a high metastatic potential. Surgical excision remains the primary treatment modality, with advanced reconstructive surgery techniques employed for defect repair. Materials and methods. We present the following clinical case. A 60-yearold female patient exhibited an extensive post-burn scar on her back, which was sustained at the age of fifteen. A clinical examination revealed an infiltrative-ulcerative tumor measuring 27x21 cm located on the right scapular region. The diagnosis was squamous cell carcinoma of the back, stage T3N2M0, clinical stage IVa, group II. Treatment involved tumor excision with the subsequent defect repair using a free split-thickness skin graft. The postoperative period was uneventful. Results and discussion. The free skin graft achieved over 95% uptake, successfully covering the wound surface. Prophylactic lymph node dissection demonstrated no impact on recurrence-free survival in the absence of regional metastases. Conclusion. SCC arising within burn scars tends to exhibit a more aggressive clinical behavior and is often diagnosed at advanced stages. To prevent malignant transformation of burn scars, we recommend meticulous wound care with protection against trauma and early skin grafting. Any alterations indicating a potential malignant transformation warrant excisional biopsy or radical excision. Patients require close monitoring post-treatment for the early detection of metastases.